Determination of the Best Quality of Sappan Bark Kombucha Drink Based on Its Sensory Characteristic - Pratama, Santi; Sinamo, Karina Nola; Ginting, Sentosa; Karo-Karo, Terip (Indonesian Journal of Agricultural Research, 2022)
Kombucha secang is a fermented drink of Acetobacter xylinum and Saccharomyces cerevisiae with the addition of sappan bark. The purpose is to get the best quality of kombucha secang drink based on sensory characteristics with differences in the amount of sugar and fermentation time. The research was conducted using a factorial completely randomized design method. The factors were the addition of sugar concentration (G = 10%, 20% and 30%) and the fermentation time (F = 4, 7, 10 and 13 days). The parameters observed were raw material characteristics, sensory tests in the form of color, aroma, taste, viscosity, general acceptance, and the best drink quality with further tests of antioxidant activity, alcohol content, and total plate number. The best quality characteristic of the kombucha secang drink was the addition of 20% sugar concentration and 10 days of fermentation time with antioxidant activity IC50 of 31.9744 ppm, the alcohol content of 0.1967%, and total plate count (TPC) of 7.6 x 105 CFU/ml.